Integrasi Prinsip Ekonomi Islam dalam Praktik Green Economy untuk Meningkatkan Pertumbuhan Ekonomi Berkelanjutan (Studi Kasus pada Sektor Kuliner Halal di Kota Bengkulu) - Nabilah Nur Atikah; Romi Adetio Setiawan; Makmur (Universitas Muhammadiyah Surabaya, 2026)
The development of the halal culinary sector in Indonesia has shown significant growth along with increasing public awareness of the consumption of halal and environmentally friendly products. However, halal culinary businesses in many regions still face challenges in integrating Islamic economic values ​​with the concept of a green economy oriented towards environmental sustainability. This study aims to analyze how halal culinary businesses in Bengkulu City interpret and apply Islamic economic principles such as halal, thayyib, amanah, justice ('adl), and the prohibition of israf in green economy practices. This study used a qualitative approach with a phenomenological method to explore the subjective experiences of halal culinary businesses. Data were obtained through in-depth interviews, field observations, and documentation of six halal culinary businesses and four consumers in Bengkulu City. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results show that most businesses understand the principles of halal and cleanliness (thayyib) in managing raw materials and production processes. However, the implementation of green economy practices such as food waste management, energy efficiency, and the use of environmentally friendly packaging is still suboptimal. The main challenges faced by businesses include limited knowledge, the cost of implementing environmentally friendly technologies, and a lack of supporting regulations. Nevertheless, businesses that have integrated Islamic economic values ​​with environmentally friendly practices have shown improved business image and consumer trust. This study concludes that integrating Islamic economic principles with the green economy has the potential to support sustainable economic growth in the halal culinary sector in Bengkulu City.